PENINGKATAN KUALITAS TAPE DARI BUAH SUKUN (Artrocapus altilis) DENGAN PENAMBAHAN BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI PEWARNA ALAMI - Romadhan, Muhammad Fauzi; Wahyuni, Dwi Suci; Kurnia, Arlinda; Anisa, Nanda; Habisukan, Ummi Hiras (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2024)
One of the basic types of carbohydrate sources that are usually used as ingredients for making tape is breadfruit. Breadfruit is a multipurpose plant that has economic value because it produces fruit with high nutritional content. Therefore, one of the preparations suitable for breadfruit is the manufacture of tape, the processing of breadfruit tape is hoped by researchers to improve the quality of breadfruit so that attractive fermented food products are created. To increase consumer acceptance by providing more attractive dyes. Natural dyes are used in the manufacture of tape as an alternative to improve the quality of tape. One of the plants that can be used as natural dyes is red dragon fruit which contains the pigment betacyanin which gives a purplish-red color. The steps for making tape from breadfruit (Artrocapus altilis) with the addition of red dragon fruit (Hylocereus polyrhizus) as a natural dye follow the stages of Velayati (2021) which have been modified into seven stages. The duration of fermentation actually affects the color, taste, aroma, texture and pH level. This is because the longer the fermentation time will affect the alcohol content present. In addition, it is necessary to pay attention to packaging so that air cannot enter and interfere with the fermentation process. Because the cause of the breadfruit tape results taste bland because the enzymes in the yeast Saccharomyces cereviceae do not break if there is air that interferes with the enzyme breaking process. Tape that is ready for consumption must pass an organoleptic test to determine the panelist's preference level. From the results of organoleptic tests on 10 untrained panelists, it was found that breadfruit tape with the addition of dragon fruit as a natural dye in terms of aroma, texture, taste and color was acceptable to the public.